KINERJA APARATUR SIPIL NEGARA (ASN) DALAM MEMBERIKAN PELAYANAN PUBLIK DI KANTOR DISTRIK ALAMA KABUPATEN MIMIKA - MULUGOL, ENEAS; MAMENTU, MAICHAEL; KIMBAL, ALFON (JURNAL ADMINISTRASI PUBLIK, 2020)
This study aims to determine performance of state civil apparatus in public service andimplementation of public service duties at the office of the sub- district of Loa Janan. This researchis a descriptive research with qualitative approach. Data obtained through interviews, observationand literature review, and analyzed with interactive model. The result of the research shows that it isnot optimal because there are still public complaints about the work of the State Civil Apparatus,namely the apparatus attitude, the transparency of the service process, the timeliness and the mechanismor the procedure of service and the lack of discipline of the apparatus.Keywords : Performance of the State Civil Apparatus in providing public services